Западная Европа XI-XIII веков: [эпоха, быт, костюм] / А. Л. Ястребицкая - Ястребицкая Алла Львовна (Искусство, 1978)
Экземпляры: КХ (20240317) / Инвентарный номер: 688506 / Сис.шифр: 9(4)1 / Авт.знак: Я 85 / ГРНТИ: 03 / ББК: 63